Eigenfunction Expansions of Impulsive Dynamic Sturm-Liouville Problems - Bilender Allahverdiev; Hüseyin Tuna; Hamlet A Isayev (Sahand Communications in Mathematical Analysis)
This paper studies impulsive dynamic Sturm-Liouville boundary value problems. The existence of a countably infinite set of eigenvalues and eigenfunctions is proved and a uniformly convergent expansion formula in the eigenfunctions is established.